The Revelation of Al-Fatihah: A Tafsir-Based Analysis of Its Context, Themes and Societal Impact - Nusaibah, N; Sanuri, S (QiST: Journal of Quran and Tafseer Studies, 2025)
Al-Fatihah, known as "The Opening," is the first chapter of the Quran and serves as a cornerstone of Islamic worship and theology. Revealed in Mecca during a time of significant struggle against polytheism and social injustice, this chapter emphasizes the oneness of God (Tawhid) and addresses the challenges faced by early Muslims. Its recitation fosters unity and identity among believers, reinforcing communal bonds in a divided society. The study aims to explore the revelation, theme, and societal impact of al-Fatihah through a library-based tafsir approach. Primary sources such as al-Qurtubi's al-Jāmi' li Aḥkām al-Qur'ān, Ibn Kathīr's Tafsīr al-Qur'an al-'Azīm, Ibn al-Qayyim's Madārij al-Sālikīn, and contemporary tafsir by al-Sa'dī and Ibn 'Uthaymīn are analyzed alongside modern scholarship. The context of Al-Fatihah's revelation highlights its role in providing spiritual clarity and moral guidance. The chapter's themes of mercy, resilience, and divine guidance offer hope to believers, emphasizing the importance of a direct relationship with Allah. Its recitation in daily prayers reinforces Muslim identity across culture and context. By filling the gap in existing research on the historical and theological context of its revelation, this study contributes to a more comprehensive understanding of the enduring role in shaping Muslims' spirit and communal life. This article aims to enhance understanding of Al-Fatihah's historical context and enduring significance in shaping the faith and practices of Muslims.